2012
DOI: 10.5539/ells.v2n3p18
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-centered and/or Student-centered Learning:English Language in Iran

Abstract: This paper reports on research findings on leaner-centered approach compared to teacher-centered approach in teaching English grammar as a foreign language in Iranian high school context. It shows the need for grammar instruction in English language classes when roughly all education efforts are bottom-up explicit approach. One could compare and contrast these two learning approaches and try to evaluate the effectiveness of them. To this end, a cohort of 60 male homogeneous students at a junior high school in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 14 publications
(7 reference statements)
3
59
1
3
Order By: Relevance
“…The results of the present study suggest that a significant improvement in the performance of the treatment group in question could indicate the use of audio-visual aids and CALI. Our results agree with similar outcomes of some other studies (Zohrabi & Torabi, 2012;Hopp, 2013;Czerwon, et al, 2013;Clément, et al, 2013;Sadeghi & Dousti, 2013).…”
Section: Conclusion and Recommendationssupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the present study suggest that a significant improvement in the performance of the treatment group in question could indicate the use of audio-visual aids and CALI. Our results agree with similar outcomes of some other studies (Zohrabi & Torabi, 2012;Hopp, 2013;Czerwon, et al, 2013;Clément, et al, 2013;Sadeghi & Dousti, 2013).…”
Section: Conclusion and Recommendationssupporting
confidence: 83%
“…(Hopp, 2013: p. 53) Many experiments investigated the teaching approaches' effect. Using 2 different teaching manipulations, the findings of using both leaner-centered approach and teacher-centered approach in teaching English grammar as a foreign language were compared by Zohrabi & Torabi (2012). Sixty subjects in question were divided into an experimental group and a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher-centered content was reported in Iran while a relationship was observed between group work in the class vocabulary learning in other countries (Zohrabi, 2012). This emphasized a direct relationship in the effectiveness of different treatments and learners' vocabulary learning.…”
Section: Second Research Question Is There Any Relationship Between Tmentioning
confidence: 94%
“…The participants of the study were 60 male students of intermediate level. Zohrabi et al (2012) concluded that teacher-centered process was supported for the development of grammar learning in Iranian EFL learners. They further found that practically Teacher-Centered Learning (TCL) is more acceptable and applicable in Iranian English language teaching system.…”
Section: Communicative Language Teaching (Clt)mentioning
confidence: 99%
“…Moreover, CLT could be more applicable in the Malaysian secondary schools. Zohrabi, Torabi, & Baybourdiani (2012) conducted a quantitative research to find out the possibility to integrate student-centered learning with teacher-centered learning among the EFL learners of Iran. The participants of the study were 60 male students of intermediate level.…”
Section: Communicative Language Teaching (Clt)mentioning
confidence: 99%